2021
DOI: 10.1002/brb3.2075
|View full text |Cite
|
Sign up to set email alerts
|

Nervonic acid level in cerebrospinal fluid is a candidate biomarker for depressive and manic symptoms: A pilot study

Abstract: Objective Our previous metabolomics study showed that the plasma nervonic acid levels were higher in patients with major depressive disorder (MDD) than those in healthy controls and patients with bipolar disorder (BD). To examine whether the nervonic acid levels differ in the central nervous system, we investigated the levels in the cerebrospinal fluid (CSF) of patients with MDD, BD, and healthy controls. Methods Nervonic acid levels in CSF were measured by gas chromatography time‐of‐flight mass spectrometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Some scholars even found that some biomarkers of renal insufficiency can be referenced to predict the depressive and anxious status in SLE patients, despite that they fail to show value in diagnosis of nephritis (46). The levels of nervonic acid in plasma and cerebrospinal fluid were a satisfied biomarker for forecasting depressive symptoms (47,48). In light of this, nervonic acid is not only associated with the renal impairment in SLE patients, but also correlated with the depressive state.…”
Section: A B Cmentioning
confidence: 97%
“…Some scholars even found that some biomarkers of renal insufficiency can be referenced to predict the depressive and anxious status in SLE patients, despite that they fail to show value in diagnosis of nephritis (46). The levels of nervonic acid in plasma and cerebrospinal fluid were a satisfied biomarker for forecasting depressive symptoms (47,48). In light of this, nervonic acid is not only associated with the renal impairment in SLE patients, but also correlated with the depressive state.…”
Section: A B Cmentioning
confidence: 97%
“…Both healthy and unhealthy workers were concurrently recruited and analyzed in the present study. Objective assessments of participants with current psychiatric treatment and psychiatric history were not conducted, which could be a limitation [ 34 , 35 ]. Finally, the influence of memory bias could not be corrected, because self-administered scales were utilized in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, valeric acid was also found to be reduced in MDD patients, which could be explained by dysregulation of the brain-gut-microbiota axis or increased N-methyl-d-aspartate (NMDA) receptor activity [ 46 ]. On the other hand, nervonic acid, a monounsaturated fatty acid important for myelin synthesis, has been elevated in patients with MDD [ 26 ] but cerebrospinal fluid nervous acid levels did not differ between MDD patients and healthy controls [ 53 ].…”
Section: Reviewmentioning
confidence: 99%